An epidemiology of animal bite cases attending tertiary care centre of Bangalore Medical College and Research Institute, Bengaluru: a retrospective study - Sreenivas, Navya Sri; Sakranaik, Saraswathi; Sobagiah, Ranganath Thimmanahalli; Kumar, Anil (International Journal Of Community Medicine And Public Health, 2017)
Background: Rabies is a viral zoonosis. In up to 99% of cases, domestic dogs are responsible for rabies virus transmission to humans. About 30% of the victims of dog bites are children under the age of 15. Ironically, all these problems are preventable by effective vaccination. However, for an effective prevention programme, it is important to understand the epidemiology of animal bite cases. The objective of the study was to assess the epidemiological pattern of animal bite cases attending anti-rabies clinic. Methods: A record based retrospective study was conducted from April to May 2016 by reviewing the records of one year in anti-rabies clinic. Results: In the study out of 2850 bite victims, 78% were males and about 21, 54% were in the age group of 20-29 years. 97% of cases were bitten by dog. Based on area wise distribution majority of the bite victims were from Bangalore west (49.5%), among them 23% was referred for Immunoglobulin. The study also showed that majority of paediatric cases were reported more during the month of April and May. Conclusions: In our study we found that majority of cases were reported among the paediatric age group during summer vacations. Hence education should be given in the community as well in schools for primary prevention of animal bite.